Peningkatan Hasil Belajar Siswa Pada Pembelajaran Tematik Terpadu dengan Pendekatan Contextual Teaching and Learning (CTL) di Sekolah Dasar - Gustiani, Putri; Miaz, Yalvema (Universitas Negeri Padang, 2022)
The purpose of this study was to describe the improvement of student learning outcomes using the Contextual Teaching and Learning approach in integrated thematic learning in grade IV elementary schools. Integrated thematic learning is learning that uses themes in the learning process. This research method, using classroom action research methods with qualitative and quantitative approaches. Where this research was conducted on the fourth grade students of SDN 03 Pasaman, amounting to 20 people consisting of 10 male students and 10 female students. The results showed an increase in student learning outcomes in integrated thematic learning using the Contextual Teaching and Learning approach. From the average value in cycle I, 74% to 88% in cycle II.